Characterization of transcription of genes involved in hairy root induction on pRi1724 core-T-DNA in two Ajuga reptans hairy root lines - Tanaka, N (Plant science : an international journal of experimental plant biology, 1998)
The detailed status of the transcription of genes on pRil724 T-DNA in two independent hairy root lines of the plant Ajuga reptans, Ar-4 and Ar-24, which have several different characteristics, was obtained by Northern blotting and a reverse transcription-polymerase chain reaction (RT-PCR) analysis. In the Northern blotting analysis DNA fragments corresponding to the putative open reading frames (ORFs) as probes, transcripts from putative ORFs 10 (1724rolA), 11 (1724rolB), 12 (1724rolC), 13a and 14, which are homologs to each ORF on pRiA4, were detected in both hairy root lines, whereas no transcripts derived from ORF 13 were detected. The transcription of ORF 13 was, however, detected in the RT-PCR analysis, suggesting a minor expression of ORF 13. All of the putative ORFs were transcribed with their expected directions, since DNA fragments were amplified when the antisense primers were employed in the reverse transcription. We also found that different transcripts with a reverse direction were present at the locations of 1724rolA, 1724rolC and ORF 13a, because the DNA fragments were amplified from the templates when their sense primers were used in the reverse transcription